A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Middle Palaeolithic occupation of the southern North Sea Basin: evidence from the Sandscaping sediments emplaced on the beach between Bacton and Walcott, Norfolk, UK - Rob Davis; Nick Ashton; Rachel Bynoe; John Craven; Rob Ferguson; Ian Gardner; Tim Grimmer; Claire Harris; Marcus Hatch; Colin Johnson; Joanne Leonard; Simon Lewis; et al. (Journal of Quaternary Science, 2023)
During the summer of 2019, the Bacton to Walcott Coastal Management Scheme involved the emplacement on to the foreshore of 1.8 million cubic metres of sand and gravel dredged from the submerged sediments of the Palaeo‐Yare in the southern North Sea 11 km off Great Yarmouth. During the following 2‐year period, an active group of collectors identified Palaeolithic artefacts eroding from these sediments, including Levallois cores and flakes, and cordiform handaxes. In this paper, we present an analysis of the lithic artefacts, and consider the relationships between the different elements of the assemblage. We discuss its significance in the context of the Middle Palaeolithic record of northwest Europe and the light it shines on the human occupation of the submerged landscape of the southern North Sea during the later Middle Pleistocene. Interrogation of beach survey data shows the reworking of these sediments to the southeast towards Happisburgh where archaeologically significant exposures of the Cromer Forest‐bed Formation are located. The implications of the introduction of a Middle Palaeolithic assemblage to this stretch of the North Norfolk Coast are considered, highlighting the importance of continuing dialogue between researchers, local authorities and local communities for capturing information and monitoring this critical Palaeolithic resource.

Behavioral assessment of in-air hearing range for the Pacific walrus (Odobenus rosmarus divergens) - Colleen Reichmuth; Jillian M. Sills; Arial Brewer; Lisa Triggs; Rebecca Ferguson; Erin Ashe; Rob Williams (Polar Biology, 2020)